2011
DOI: 10.1017/s000711451100081x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of intra- and inter-individual metabolite variation in plasma metabolite profiles of cats and dogs

Abstract: The purpose of the present study was first to identify drivers of variance in plasma metabolite profiles of cats and dogs that may affect the interpretation of nutritional metabolomic studies. A total of fourteen cats and fourteen dogs housed in environmentally enriched accommodation were fed a single batch of diet to maintain body weight. Fasting blood samples were taken on days 14, 16 and 18 of the study. Gas chromatography -mass spectrometry (GC-MS), liquid chromatography (LC) -MS/MS and solid-phase extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 11 publications
(14 reference statements)
1
24
0
Order By: Relevance
“…It is possible to speculate that the identification of phosphatidylcholine as a robust marker of breed difference may indicate differences in lipid metabolism and lipid functionality between breeds. This finding parallels work which identified a group of lipids showing high inter-individual variance within individuals of both dogs and cats (Colyer et al 2011 ). The structural similarities and possible biochemical relationships are shown in Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It is possible to speculate that the identification of phosphatidylcholine as a robust marker of breed difference may indicate differences in lipid metabolism and lipid functionality between breeds. This finding parallels work which identified a group of lipids showing high inter-individual variance within individuals of both dogs and cats (Colyer et al 2011 ). The structural similarities and possible biochemical relationships are shown in Fig.…”
Section: Resultssupporting
confidence: 89%
“…It is likely that blood-based metabolite fingerprinting may provide more relevant data for determining “host-derived” endogenous metabolic variance between dog breeds. Previously, the plasma metabolome has provided data relevant to specific metabolic adaptations of species and also has identified differences between individuals (Allaway et al 2013 ; Colyer et al 2011 ). However, these data were derived from studies undertaken under controlled environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In a targeted metabolite profiling study investigating individual variability when fed the same diet, metabolites that showed high inter-individual and low intra-individual variance were also related to lipid/sterol chemistry (Colyer et al 2011). These confirm other non-metabolomics studies: for example total plasma cholesterol and triacylglyceride concentrations have been shown to vary between canine breeds and with diet (Downs et al 1993; Usui et al 2014) and Beagles and Greyhounds have been shown to have different pulmonary surfactants (Clercx et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Further research is required to determine the potential for canines with diabetes to be used as an alternative animal model of human T1D 10 , and if metabolomic analysis may identify novel biomarkers of the disease. While metabolomic profiles have been studied in healthy dogs 11 , 12 and in several disease states, including inflammatory bowel disease 13 and degenerative valvular disease 14 , information from an untargeted metabolomics assessment of diabetic dogs is lacking. With this study, we evaluated the metabolomic profiles of fasted diabetic versus healthy control dogs, and hypothesized that diabetic dogs have metabolomic perturbations similar to those reported in human T1D patients, including alterations in carbohydrates, branched-chain AA and FA.…”
Section: Introductionmentioning
confidence: 99%